PENGELOLAAN ASET TETAP BERDASARKAN METODE REVALUASI TERKAIT DENGAN PERENCANAAN PAJAK PENGHASILAN (STUDI PADA RUMAH SAKIT YADIKA PONDOK BAMBU) - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA; Try Masroyany (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This study aims to provide a viewof the fixed assets measurement using the revaluation method for the fairness of financial statements and their impact on savings on entity’s taxes. The research was conducted in descriptive qualitative using secondary data from the research namely Rumah Sakit Yadika Pondok Bambu in 2018. The result of the study show that using the revaluation method in addition to measuring and presenting fixed assets can reflects the real conditions of the assets and can also save income tax for entity.